SIgA, TGF-β1, IL-10, and TNFα in Colostrum Are Associated with Infant Group B Streptococcus Colonization - Le Doare, Kirsty; Bellis, Katie; Faal, Amadou; Birt, Jessica; Munblit, Daniel; Humphries, Holly; Taylor, Stephen; Warburton, Fiona; Heath, Paul T.; Kampmann, Beate; Gorringe, Andrew (Frontiers in Immunology, 2017)
Background Group B Streptococcus (GBS) is a major cause of mortality and morbidity in infants and is associated with transmission from a colonized mother at birth and via infected breastmilk. Although maternal/infant colonization with GBS is common, the majority of infants exposed to GBS remain unaffected. The association between breastmilk immune factors and infant colonization and disease prevention has not been elucidated. Objectives We have investigated the association between SIgA and cytokines in breastmilk and infant GBS colonization and clearance. Methods Mother/infant GBS colonization was determined in a prospective cohort of 750 Gambian mother/infant pairs followed to day 89 of life. Anti-GBS secretory IgA bound to the surface of whole bacteria was assessed by flow cytometry and a panel of 12 cytokines quantified by mesoscale discovery in colostrum, breastmilk and serum. Results Compared with infants receiving low anti-GBS SIgA in colostrum, infants receiving high anti-GBS SIgA were at decreased risk of GBS colonization for serotypes III and V. Infants colonized at day 6 were twice as likely to receive colostrum with high TGF-β1, TNFα, IL10, and IL-6 compared to uncolonized infants. Infants receiving high colostral TGF-β1, TNFα, and IL-6 had two-fold enhanced GBS clearance between birth and day 89. Conclusion Our results suggest that the infant GBS colonization risk diminishes with increasing anti-GBS SIgA antibody in breastmilk and that key maternally derived cytokines might contribute to protection against infant colonization. These findings might be leveraged to develop interventions including maternal vaccination that may reduce infant GBS colonization.